Long Covid active case finding study protocol: A co-produced community-based pilot within the STIMULATE-ICP study (Symptoms, Trajectory, Inequalities and Management: Understanding Long-COVID to Address and Transform Existing Integrated Care Pathways). - Nisreen A Alwan; Donna Clutterbuck; Marija Pantelic; Jasmine Hayer; Lere Fisher; Lyth Hishmeh; Melissa Heightman; Gail Allsopp; Dan Wootton; Asad Khan; Claire Hastie; Monique Jackson; et al. (PLoS ONE, 2023)
Background and aim Long Covid is a significant public health concern with potentially negative implications for health inequalities. We know that those who are already socially disadvantaged in society are more exposed to COVID-19, experience the worst health outcomes and are more likely to suffer economically. We also know that these groups are more likely to experience stigma and have negative healthcare experiences even before the pandemic. However, little is known about disadvantaged groups' experiences of Long Covid, and preliminary evidence suggests they may be under-represented in those who access formal care. We will conduct a pilot study in a defined geographical area in London, United Kingdom to test the feasibility of a community-based approach of identifying Long Covid cases that have not been clinically diagnosed and have not been referred to Long Covid specialist services. We will explore the barriers to accessing recognition, care, and support, as well as experiences of stigma and perceived discrimination. Methods This protocol and study materials were co-produced with a Community Advisory Board (CAB) made up primarily of people living with Long Covid. Working with voluntary organisations, a study leaflet will be distributed in the local community to highlight Long Covid symptoms and invite those experiencing them to participate in the study if they are not formally diagnosed. Potential participants will be assessed according to the study's inclusion criteria and offered the opportunity to participate if they fit them. Awareness of Long Covid and associated symptoms, experiences of trying to access care, as well as stigma and discrimination will be explored through qualitative interviews with participants. Upon completion of the interviews, participants will be offered a referral to the local social prescribing team to receive support that is personalised to them potentially including, but not restricted to, liaising with their primary care provider and the regional Long Covid clinic.